'Experimental Union' and Baltic Sea cooperation: the case of the European Union's Strategy for the Baltic Sea Region (EUSBSR). Issue 1 (1st January 2018) - Gänzle, Stefan
ABSTRACT: In the past, Baltic Sea cooperation has been characterized by a plethora of actors, embracing a wide range of policy objectives, such as the establishment of a good environmental status for the regional sea. In 2009, the European Council endorsed the European Union's (EU) Strategy for the Baltic Sea Region (EUSBSR) as a new tool in the repertoire of Cohesion Policy and European Territorial Cooperation (ETC). The EUSBSR seeks to foster cross-sectoral coordination and functional cooperation in policy areas of 'macro-region-level' relevance, such as transport infrastructure, economic development and environmental protection – thus projecting a 'soft space' of transnational Baltic Sea cooperation. Although firmly placed under the so-called 'Three No's', that is, the requirement of no additional EU funding, institutions and legislation, a lean governance architecture at the macro-regional level has emerged over time and the strategy mobilizes actors from all tenets of the EU's multilevel governance system, including the EU itself, its member and adjacent partner states, as well as subnational authorities and civil society. Drawing on the lens of experimentalist governance, this paper analyzes the underlying mechanisms that allow it to be gauged to what extent the Baltic Sea 'soft space' has solidified over the past decade. It also shows that the EUSBSR effectively rebalances EU transnational and intergovernmental regional cooperation in the Baltic macro-region.